PENGARUH BRAND PERSONALITY DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE DI QUEEN IPHONE KOTA BENGKULU - Wati, Zelin Widia; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The purpose of this study is to determine the influence of Brand Personality on product purchasing decisions at the Queen iPhone Store in Bengkulu City. To determine the influence of lifestyle on product purchasing decisions at the Queen iPhone Store in Bengkulu City To determine the influence of Brand Personality and lifestyle on product purchasing decisions at the Queen iPhone Store in Bengkulu City. This type of research is a quantitative approach. The method used in this study is a descriptive method. The population in this study were all consumers of the Queen iPhone Store in Bengkulu City, Bengkulu, whose number is unknown. the sample in the study was 140 people. Based on the results of the study and discussion on the Influence of Brand personality and Lifestyle on purchasing decisions for Queen Iphone in Bengkulu City, it has been described previously, it can be concluded that the tSig value for the Brand personality variable (X1) is 0.000. So it can be concluded that tSig <Sig (0.000 <0.050) means that Ha is accepted and H0 is rejected, that the Brand personality variable influences the purchasing decision for Queen Iphone in Bengkulu City. The tSig value for the Lifestyle variable (X2) is 0.000. So it can be concluded that tSig <Sig (0.000 <0.050) means that Ha is accepted and H0 is rejected, that the Lifestyle variable influences the purchasing decision for Queen Iphone in Bengkulu City. The hypothesis test above can be seen for the Brand personality variable (X1), and Lifestyle (X2) the Fsig value = 0.000. So it can be concluded that FSig<Sig (0.000<0.050) means Ha is accepted and H0 is rejected, that each variable has a significant influence on purchasing decisions (Y) at Queen Iphone, Bengkulu City. Keywords: Influence of Brand Personality, Lifestyle, Purchasing Decisions